(untitled) (International Journal of Built Environment and Sustainability, 2017)
Researchers have identified defects in the physical environments in which they interact and play, which has resulted in a decline the expected values initiated in both the social, physical and psychological developments. The role of playground in the development of adolescent’s health, moral and social standard has attracted lower interest in the recent time. The adolescent sense of community relates to a positive experience in the community open space setting such as playground and social well-being with their peers in general. Over time, little efforts have been initiated by the researchers towards these phenomena. This current study fills the gap by examining the adolescents’ sense of community through a quantitative survey via appraisal of the quality of community playground, emotional connection and effects of their participation in playground activities on ameliorating the delinquents’ behavior and social vices. Completed survey questionnaires retrieved from a total number of 69 purposive respondents who are adolescents from three towns and analyzed through relative importance index (RII) via Likert scale. Results from the analysis indicated that adolescents’ positive attitudinal changes and reduction in social vices and delinquent’s behavior could be achieved through their involvements in quality and well-equipped playgrounds. Similarly, the significant role of sense of community in enhancing adolescent social participation in playground activities contributes to a major role in increasing their social well-being and togetherness. Thus, the study recommends appropriate future planning, design, and management of neighborhood playgrounds in Nigeria.